Generasi Z pada Pemilihan Gubernur Jawa Barat: Bagaimana Mereka Berperilaku dengan Informasi - Fadhli, Rahmat; Nurlidia, Raden Fasha; Syam, Rifqi Zaeni Achmad (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2019)
In 2018 General election, generation Z called as first-time voter who will use their right to vote. Statistic data of the 2018’s General Election Commission indicates that first-time voter in West Java Province reaching 30% of the total voters. This research described information seeking behavior among generation Z on West Java Governor Election. The purposed of this research are to identify characteristic of information needs among Z generation, identify information source used and information awareness among Z generation. This research uses qualitative approach and case study method. There are five high school students become informants in this research and uses purposive sampling techniques. The results of this study are characteristic of information needs Z generation on aspects of the context including election procedure, profile of governor candidates, campaign activities, programs offered. The frequency of information needs tends to be low and unpredictable. Information sources tend to use online sources through social media and online mass media but they also get other information from television, newspaper, sharing with friends, parents and family; In the aspect of awareness or understanding of information resources, familiarity and prior success, information packaging, cost and accessibility affects information seeking behavior of Z generation but they have obstacle to assess the quality of information. This makes Z generation easily accept hoax information or provoked on social media such as Facebook, Instagram, Youtube and Twitter.